OP0016 Osteoclast numbers in joints of rats with adjuvant arthritis are decreased by treatment with il-1ra and/or peg stnf-ri. (1st June 2001) - Feige, U; Hu, YL; Morony, S; Campagnuolo, G; Duryea, D; Bolon, B
Abstract : Background: Adjuvant arthritis (AdA) induced in Lewis rats by injection of mycobacteria in oil is characterised by marked inflammation and skeletal damage. Recent work by our group using the AdA model has shown that skeletal destruction is mediated by the osteoclast differentiation factor osteoprotegerin (OPG) ligand, 1 and that inhibition of bone loss is associated with anti-inflammatory efficacy. 2 Objectives: The current study was performed to assess whether anti-inflammatory molecules act to spare bone by regulating intra-lesional numbers of osteoclasts. Methods: AdA was induced in male Lewis rats (n = 6/group) on Day 0, and hind paw swelling developed on Day 9. Animals were treated for 7 days (Days 9–15) and then necropsied (Day 16). Therapy consisted of interleukin-1 receptor antagonist (IL-1ra) or pegylated soluble tumour necrosis factor receptor type I (PEG sTNF-RI), administered alone or in all possible combinations, at the following doses: IL-1ra, 0.2, 1.0 or 5.0 mg/kg/hr (by s.c. infusion); PEG sTNF-RI, 0.25, 1.0 or 4.0 mg/kg/day (s.c bolus). Osteoclasts were detected by an indirect immunohistochemical method for cathepsin K. Inflammation, bone erosion and osteoclast numbers were scored blindly using tiered, semi-quantitative grading scales. Results: Dose-dependent reductions in inflammation, bone erosion and osteoclast scores were observed for high doses of both anti-cytokine therapies, whether given alone or in combination. Conclusion: These data indicate that anti-inflammatory doses of IL-1ra and PEG sTNF-RI protect the structural integrity of arthritic joints by regulating osteoclast numbers. References: Kong, et al . Nature 1999;402:304 Feige, et al . Cell Mol Life Sci. 2000;57:1457